Self-assembly of antifungal agent 5-fluorocytosine and nutrient trans-p-coumaric acid furnishes a cocrystal with the potential to reduce toxicity and side effects for the drug: a case study combining theory with experiment. (16th December 2022) - Bu, Fan-Zhi; Yu, Yue-Ming; Yu, Yu; Yan, Cui-Wei; Wu, Zhi-Yong; Li, Yan-Tuan
Abstract : Cocrystallization of 5-fluorocytosine (FLCY) and trans-p -coumaric acid was first reported. Systematic studies combining theory with experiment revealed that both solubility and dissolution rate of FLCY can be down-regulated via cocrystallization. Abstract : The current work aims to take full advantage of the structural superiority and hepatoprotective effect of the nutrient trans-p -coumaric acid (TPCA) to decrease the solubility and dissolution rate of the antimycotic agent 5-fluorocytosine (FLCY) by using a co-crystallization strategy, thereby giving a novel understanding into conquering the dose-limiting hepatotoxicity induced by the quick and almost complete absorption of FLCY. To that end, FLCY–TPCA, as the first cocrystal of FLCY and phenolic acid (a nutrient of the hydroxycinnamic acid type), is orientationally self-assembled and fully characterized. The single crystal structure shows that TPCA molecules in the crystal lattice locate at the polar sites in situ of FLCY via robust hydrogen bond interaction, thus creating a vital planar construction (VPC) possessing hydrophobicity, which results in the simultaneous down-regulation for the cocrystal of solubility and dissolution rate versus the parent FLCY. The outcomes of the experiment are strongly supported by related theory research. Molecular electrostatic potential (MEP) calculation showed that the VPC polarity in the cocrystal is lower than that of free FLCY, which conforms with the reduction in polarity due to intensifying hydrogen-bond energy based on topology analysis with atoms in molecules (AIM) theory, hence conferring a conspicuous improvement in hydrophobicity on the cocrystal. Furthermore, the molecular planarity analysis based on Multiwfn's wave function calculation module confirms the convergence in planarity at a two-dimensional infinite level, which undoubtedly contributes to forming a tight three-dimensional supramolecular superposition landscape, corresponding with the coinstantaneous reinforcement of π–π stacking interaction evidenced by the reduced density gradient (RDG), and all these results further support the fact that the hydrophobicity of the FLCY–TPCA cocrystal is significantly enhanced. As a result, the current contribution exemplifies a feasible cocrystallization strategy using integrated experimental and systematic theoretical approaches to overcome the intractable toxicity issues of antifungal agents.